If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 28 + 2x = 6x Solving 28 + 2x = 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 28 + 2x + -6x = 6x + -6x Combine like terms: 2x + -6x = -4x 28 + -4x = 6x + -6x Combine like terms: 6x + -6x = 0 28 + -4x = 0 Add '-28' to each side of the equation. 28 + -28 + -4x = 0 + -28 Combine like terms: 28 + -28 = 0 0 + -4x = 0 + -28 -4x = 0 + -28 Combine like terms: 0 + -28 = -28 -4x = -28 Divide each side by '-4'. x = 7 Simplifying x = 7
| 10x+4=29 | | -4.9t^2+19.6t+58.8=0 | | 6(y-5)=-6 | | 5(y+3)=55 | | b^2-4*b+4=0 | | 8x-32=18+6x | | 2x+8-4x-15=16+8x-2-3 | | (3x+6)= | | y=(3x/12)+105 | | 2(x-6)+3x=8 | | 3x+30=90 | | (x^2+2x+1)(x^2+5x+4)=0 | | y=3x/12+105 | | 18-2x=2x+2 | | (y+5)(y^2-5y+25)= | | 1+6x-3x=19 | | 3x+35=13x-56 | | 4*1/2-1/3 | | 6x+17=65+3x | | (3x+30)= | | (x+-7)(x+-7)=14x | | 2(a-2)=-(a-1)/(a-4) | | X^2(5x+3)=26x | | 4x-4=2x+14 | | 1/3+2x=5/12 | | 8X-5Y-3=0 | | 50=9x+5 | | 3(2x-1)=2(4x-7) | | 0.3x+33.6=51 | | 7x-10=x+2 | | 7.3x-5.8+2.5x= | | F(x)=2x^2+5x+9 |